Body on fire anti-inflammatory cookbook : your guide to eating plant foods that fight disease - Aggarwal, Monica; Rao, Jyothi (Book Publishing Company, 2022)
"This companion volume to Body on Fire reiterates essential concepts about the nature of inflammation and its relationship to chronic illness, offers insights into why certain foods are health-supporting, and provides a how-to-start manual that features an abundance of easy-to-make recipes. The main goal is to calm inflammation and reduce the risk of illness. While there are multiple steps involved with healing, nutrition should be the first one to turn to. Combined with a renewed focus on sleep, movement, and an unstressed mind, Drs. Aggarwal and Rao provide natural solutions for regaining health. Guidance, encouragement, and sound advice are offered on everything from the best times to eat and which foods affect sleep, exercise, and outlook to rediscovering the joys of cooking and budget-friendly options. The recipes use minimum amounts of salt and oil, are nutrient-dense as well as universally appealing, and deliver a boost to your health with each flavorful bite." -- Amazon.